Enforcement of Maternity Leave Rights for Female Workers under Labor Law - Octwelfth, Florentina Ezrahi; Rasji, Rasji (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The protection of maternity leave rights for female workers represents an embodiment of the principles of social justice and humanity as mandated in Article 27(2) of the 1945 Constitution. However, in practice, violations of these rights continue to occur across various employment sectors. This study aims to analyze the legal provisions governing maternity leave rights under Law No. 13 of 2003 on Manpower and to evaluate the extent to which their implementation reflects the principles of justice, legal certainty, and humanity. Employing a normative juridical approach through the analysis of primary and secondary legal materials as well as industrial relations court cases, the study finds that although the normative framework provides clear legal protection, its implementation remains weak due to inadequate supervision, low legal awareness, and persistent gender bias in the workplace. In conclusion, the Indonesian labor law system formally upholds legal certainty but has yet to fully achieve substantive justice and humanitarian protection for pregnant female workers.